ISSUES AND METHODS OF DETERMINING ZAKAT ON BUSINESS - Mohamad Naimi Mohamad Nor,; Dzarfan Abdul Kadir,; Mohamad Zaidi Azizan, (Journal of Islamic, Social, Economics and Development, 2024)
A financial statement is a document prepared by a company to report the current financial position and performance of the business over a period of time. It needs to be prepared according to the accounting standards. These financial statements are important for users to make business and investment decisions. In addition to being important for users to make business and investment decisions, these financial statements are also used to determine the amount of zakat on business. However, there are some differences and interpretations in determining the amount of zakat on business. The objective of this study is to identify the issues in determining the type of assets in zakat calculations for businesses. Furthermore, this study also aims to evaluate the asset classification method for zakat on business applied by zakat institution. This study uses information obtained from several forms of documents, whether in the form of print or online sources, that are available in the public domain. This article raises the possibility of reviewing and enhancing the asset-related accounting framework for zakat in order to better serve zakat's objectives.